Arabic translation and cultural adaptation of a characteristics of resilience in sports teams inventory questionnaire: A cognitive interview study - Alyousef, Ammar Salem (International Journal of Innovative Research and Scientific Studies, 2025)
This paper aims to enhance athlete well-being, training, and team performance by translating and culturally adapting a validated version of the Characteristics of Resilience in Sports Teams Inventory (CREST) for Arabic-speaking teams. This study used a convenience sample of 16 Arabic-speaking coaches (mean age: 41.81 years; experience: 12.44 years) and followed a structured cross-cultural adaptation process, including cognitive interviews, forward translation, synthesis, back-translation, and expert review. Cognitive interviews were conducted in three rounds. Participant characteristics were summarized using descriptive statistics, with continuous variables reported as means and standard deviations and categorical variables as frequencies and percentages. The translation and cultural adjustment of the questionnaire into Arabic incorporated slight language revisions recommended by the panel of experts. Participants unanimously agreed that the resulting Arabic version of the Characteristics of Resilience in Sports Teams Inventory (CREST) was culturally suitable and clearly expressed the original meaning of each questionnaire item. After its successful translation and cultural adaptation into Arabic, the CREST was ready for use in the Arabic context. This development opens opportunities for extensive research and tailored performance optimization strategies, potentially enhancing player welfare and development within Arabic-speaking sports communities.